Study of Light Intensity in Riparian Zone of Teak Production Forest in KHDTK Cemoro Modang - Agung, Agung Wahyu Nugroho; Heru , Heru Dwi Riyanto (Jurnal Wasian, 2020)
Vegetation is one of the factors that influence the protection function of the riparian zone. Riparian vegetation in teak production forests is dominated by teak plantation with low species diversity. Rehabilitation is needed to increase the role of vegetation in protecting riparian zone. Data and information of light intensity is required to support the success of rehabilitation. Light intensity is a significant factor for photosynthesis which impacts on the survival, growth and adaptation of a vegetation. The varying light intensity in the riparian zone due to diverse land cover becomes a challenge in rehabilitating this area. This study aims to identify light intensity in riparian zone of Modang River and Cemoro River in the teak production forest. Recognizing light characteristics will help in species selection to rehabilitate this area. Primary and secondary data were used in this study. Direct measurement of light intensity was carried out along riparian zone of the Modang and Cemoro Rivers by systematic sampling. A sampling plot measuring 20 x 20 meter was used as the location of the sampling point with a total of 36 plots. Climate data are obtained from field observations through the nearest climatology station. The results showed that different canopy cover causing light intensity of Modang and Cemoro rivers varies. Canopy cover in this area can be divided into canopy cover of teak forest of various ages (production plants), johar (previous rehabilitation plants), and logged-over areas. The selection of tolerant and intolerant trees is important to use as consideration for rehabilitation, in addition to other silvicultural and socio-economic considerations of the local community.